REPRESENTATION OF EDUCATIONAL VALUES IN CLOUDS MOVIE: A METAFUNCTION ANALYSIS IN MAIN CHARACTERS - Nining Krisnantari Elo Beili; Lerissa Daniela (Journey: Journal of English Language and Pedagogy, 2023)
This study examined the representation of the educational values in Clouds as presented by the four main characters, which are Zach, Amy, Sammy, and Zach's mother by utilizing the three metafunctions concepts by Kress and Leeuwen (2006) and the theory of education value by Linda and Richard in Elmubarok (2019). This study used a qualitative descriptive method. This research found that there are 10 out of 12 educational values. The researcher did not find purity and respect values. The educational values can be seen along with the four main characters' presentation in a frame by their surroundings or the clothing they are wearing, or what is known as representational metafunction. Next, how the actors interact with one another in a frame or scene through eye contact, spoken words, and actions, or what is known as interactional meta-function. And the last is through the compositional meta-function which describes how characters and objects are positioned, how much space they take up, and how well they are portrayed. Readers can adopt the morals portrayed in the movie as a good guide in daily life and be inspired to treat others well.